Inventors? Response to Firm Acquisitions - Katrin Hussinger (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2007)
Mergers and acquisitions (M&As) constitute a disruption to the working environment of the inventive labor force of the acquired company. If inventors would respond with a decline of their patent productivity or departure from the firm this can be detrimental to the innovative process within the merged entity and can be contradictory to the aims of the firm acquisition. This paper provides empirical evidence on post-merger mobility and productivity of 673 inventors employed by European acquisition targets in the years 2000 and 2001. The empirical results show that 1.) the most productive and experienced individuals stay with the merged entity; 2.) inventors that left the acquired firm are less productive in post-merger years than those that stayed with the merged entity; 3.) M&As trigger inventor mobility, but do not lead to a decline in patent productivity if compared to a control group of inventors that have not been involved in a firm acquisition.
Keywords: G34; C24; O32; 330; M&As; inventor mobility and productivity; Übernahme; Fusion; Erfindung; Wissenschaftler; Arbeitsmobilität; Patent; Produktivgenossenschaft; Europa